Does money matter for schools? - Helena Holmlund; Sandra McNally; Martina Viarengo (Institute for the Study of Labor (IZA), 2008)
There is considerable disagreement in the academic literature about whether raising school expenditure improves educational outcomes. Yet changing the level of resources is one of the key policy levers open to governments. In the UK, school expenditure has increased by about 40 per cent in real terms since 2000. Thus, providing an answer to the question as to whether such spending has an impact on educational outcomes (and whether it is good use of public money) is of paramount importance. In this paper we address this issue for England using much better data than what has generally been used in such studies. We are also able to test our identification assumption by use of a falsification test. We find that the increase in school expenditure over recent years has had a consistently positive effect on outcomes at the end of primary school. Back-of-envelope calculations suggest that the investment may well be cost-effective. There is also some evidence of heterogeneity in the effect of expenditure, with higher effects for students who come from economically disadvantaged backgrounds.
urn:nbn:de:101:1-20081126249
Keywords: I21; 330; Education; resources; Öffentliche Bildungsausgaben; Schulfinanzierung; Wirkungsanalyse; Bildungsniveau; Allgemeinbildende Schule; Großbritannien